Caracterização físico-química e reológica de licor de maracujá (Passiflora edulis), gengibre (Zingiber officinale) e capim-cidreira (Cymbopogon citratus) - Escarelli, Ana Beatriz Leandro (2024)
Liqueur is a drink with an alcohol content of between 15 and 54% by volume, at 20°C, and a sugar content greater than 30 grams per liter. It is an alcoholic drink that is simple to prepare, and its main natural components are vegetables. In addition, its industrialization can add value to family farming production. The objective of the present work was to develop a passion fruit, ginger and lemongrass liqueur in different concentrations of raw materials and characterize it in relation to the physical-chemical parameters of titratable acidity, pH, color, water activity and soluble solids content. to compare with specific liquor legislation. The rheological behavior of the formulations was also determined using a concentric cylinder viscometer. The formulations had a low soluble solids content compared to the legislation, with formulation F1 having the highest value of 23.93, a value conferred by the high content of passion fruit pulp, the pH remained low (acidic) in all formulations, varying 3.95 to 4.9, and is within the legislation for alcoholic beverages. The water activity approached the value of 1, which means high water activity in the liqueurs, as expected for simple liqueurs. The formulations present acidity, especially in the formulations with greater addition of passion fruit pulp (F1 and F2), as it is an acidic fruit, and therefore provides greater acidity to the liqueur. In terms of color, the formulations are closer to black, with formulations F1 and F2 in more yellow and red tones, and formulations F3, F4 and F5 with more green and blue tones, according to the values found in the colorimetric parameters. The experimental data presented an adjustment to the Bingham and Newton models, however, the F1 and F2 formulations did not present a good adjustment to the models, while the F3, F4 and F5 presented an excellent adjustment to the Bingham model, concluding that these fluids exhibit Binghamian non-Newtonian fluid behavior.